Patient and Family Perspectives on Statutory Duty of Candour Following Serious Adverse Patient Safety Events - Corey Adams; Lorelle Bowditch; Mia Bierbaum; Ramya Walsan; Jennifer Morris; Elizabeth Manias; Nicole Youngs; Lanii Birks; Jeffrey Braithwaite; Ashfaq Chauhan; Peter Hibbert; Ramesh Walpola; et al. (Health Expectations, 2026)
ABSTRACT Background The Statutory Duty of Candour (SDC) legally requires healthcare organisations to notify patients, families, and carers who experience a serious adverse patient safety event (SAPSE), provide an apology, and explain steps taken to prevent recurrence. However, despite growing international adoption of SDC, evidence on its implementation and impact on patients and families (‘consumers’) remains limited. This study examined consumer awareness, understanding, and lived experiences of SDC in Victoria, Australia, two years after its introduction. Methods A mixed‐methods study integrated data from an online survey and semi‐structured interviews with healthcare consumers in Victoria, Australia. Descriptive analysis was undertaken for quantitative items, while reflexive thematic analysis was applied to qualitative data from survey free‐text responses and interview transcripts. Results In total, 80 consumers participated: 72 completed the survey and 13 completed interviews, with five participating in both. Although nearly two‐thirds (61%) had no prior knowledge of SDC, over three‐quarters (78%) perceived it as useful. Among those who had experienced an adverse event, half reported that staff were not open following the incident, over half reported that no post‐incident meeting occurred, and satisfaction with meetings was low (26%). Six themes were identified: (1) Candour as Moral Reassurance; (2) Persistent Scepticism and Conditional Trust; (3) Limited Awareness and Accessibility of SDC; (4) Genuine Apology for Trust Repair; (5) Emotional Labour, Power, and the Risk of Re‐traumatisation; and (6) Demonstrating Accountability with Organisational Learning and Improvement. An overarching theme, Candour as a Relational Process for Trust, described how trust was tested, repaired, or further eroded through SDC processes following an adverse event. Conclusion SDC holds significant potential to repair trust following adverse events, but its impact depends on how it is enacted. When delivered with empathy and meaningful follow‐up, SDC supports repair of trust. However, when experienced as procedural or defensive, SDC may compound distress and further erode trust. Therefore, SDC must be embedded not just as a regulatory requirement, but as a relational and person‐centred practice for patients and families. Patient or Public Contribution Healthcare consumer representatives were part of the research team, assisting with the study design, data analysis, and article writing.